(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Cassava root (Manihot esculenta Crantz) is highly perishable and contains toxic compounds, necessitating processing and preservation to ensure safe consumption and the production of shelf-stable, value-added products. This study evaluated the effect of various processing techniques on the quality of fermented cassava flour (known as lafun in South-Western Nigeria). Cassava roots (TME 419) were processed using grated solid-state fermentation (GSSF), sliced-soaked fermentation (SSMF), and parboiled-soaked fermentation (PSMF), with products dried in a parabolic solar dryer. Flour quality was assessed based on proximate composition, cyanide content, functional properties, and pasting properties. Moisture content ranged from 11.17% - 12.86%, with the lowest in PSMF. Crude fat, protein, crude fibre, and carbohydrate contents varied from 1.17% - 2.65%, 6.16% - 7.42%, 0.41% - 0.55%, and 69.92% - 74.85%, respectively. Cyanide concentrations ranged from 1.720 - 1.780 mg/kg, indicating a 92.11% - 92.37% reduction from fresh cassava roots (22.55 mg HCN/kg). Water and oil absorption capacities ranged from 212.57% - 246.93% and 59.96% - 65.17%, respectively, with PSMF significantly higher. PSMF exhibited the highest swelling power (225.07%) and lowest water solubility (39.46%), along with the highest filling weight (0.785 g/cm³). Pasting temperature and peak time ranged from 75.48°C - 93.58°C and 4.53 - 6.97 min, with PSMF having the highest values. These results suggest that PSMF is the most effective method for producing high-quality fermented cassava flour.